2020
DOI: 10.1186/s12864-020-06972-6
|View full text |Cite|
|
Sign up to set email alerts
|

Common bean resistance to Xanthomonas is associated with upregulation of the salicylic acid pathway and downregulation of photosynthesis

Abstract: Background Common bacterial blight (CBB) caused by Xanthomonas phaseoli pv. phaseoli and Xanthomonas citri pv. fuscans is one of the major threats to common bean crops (Phaseolus vulgaris L.). Resistance to CBB is particularly complex as 26 quantitative resistance loci to CBB have been described so far. To date, transcriptomic studies after CBB infection have been very scarce and the molecular mechanisms underlying susceptibility or resistance are largely unknown. Results We sequenced and annotated the genom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 143 publications
10
23
2
Order By: Relevance
“…CBB symptoms including necrotic lesions were widely apparent on X. axonopodis -inoculated leaves of the CBB-susceptible RIL, whereas symptoms were dramatically lower in the CBB-resistant RIL. The occurrence of severe symptoms in the CBB-susceptible RIL within 14 d of pathogen inoculation mirrors the disease development timeline for other P. vulgaris genotypes [ 4 , 32 , 33 ]. The accelerated development of disease symptoms in the CBB-susceptible RIL is likely because disease inoculation experiments were performed under a constant high humidity in a controlled environment.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…CBB symptoms including necrotic lesions were widely apparent on X. axonopodis -inoculated leaves of the CBB-susceptible RIL, whereas symptoms were dramatically lower in the CBB-resistant RIL. The occurrence of severe symptoms in the CBB-susceptible RIL within 14 d of pathogen inoculation mirrors the disease development timeline for other P. vulgaris genotypes [ 4 , 32 , 33 ]. The accelerated development of disease symptoms in the CBB-susceptible RIL is likely because disease inoculation experiments were performed under a constant high humidity in a controlled environment.…”
Section: Discussionmentioning
confidence: 64%
“…The number of total DEGs across the 48 h PI period for both the CBB-resistant and CBB-susceptible RIL investigated in our study is well below the 2576 and 4502 DEGs respectively identified in BAT93 and JaloEEP558 leaf discs infiltrated with X. phaseoli pv. phaseoli [ 32 ]. The greater number of DEGs in the previous study could be due to the use of leaf discs for pathogen infiltration and subsequent incubation in water-agar for up to 48 h, conditions yielding approximately 200 DEGs across BAT93 and JaloEEP558 associated with nitrogen metabolism, as well as 10 photosynthesis genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, expression studies related to CBB resistance are still limited (Cooper, 2015 ; Shi, Chaudhary, et al, 2011 ). Recently, a first description of whole‐transcriptome changes upon infection of resistant and susceptible plants showed that resistance was associated with up‐regulation of the salicylic acid pathway and down‐regulation of photosynthesis (Foucher et al, 2020 ). Interestingly, 26 genes had a large difference of expression between the resistant and susceptible genotypes and colocalized with resistance QTLs.…”
Section: Disease Managementmentioning
confidence: 99%
“…In particular, transcriptome sequencing (RNA sequencing, RNA-seq) has contributed to important discoveries in various fields such as host–pathogen interactions. RNA-seq has been applied to common bean in interaction with bacteria [ 21 ], BCMV [ 22 ] and the fungus Fusarium oxysporum [ 23 ] but also to common bean (carrying Co-1 gene)/ C. lindemuthianum interaction [ 24 ]. In order to identify host plant response upon C. lindemuthianum infection, we characterized the transcriptome of common bean BAT93 ( Co-9 ) after infection with two strains of C. lindemuthianum leading to compatible or incompatible interactions.…”
Section: Introductionmentioning
confidence: 99%